Moving Beyond Silos in Cumulative Effects Assessment - Hodgson, Emma E.; Halpern, Benjamin S.; Essington, Timothy E. (Frontiers in Ecology and Evolution, 2019)
Many of the world’s ecosystems are experiencing a suite of changes from anthropogenic activities; the multiple stressors from those activities result in cumulative impacts. Understanding how these activities translate into ecological consequences is exceedingly challenging because of the inherent complexity within natural systems and the variability in how stressors act and species respond. While there have been substantial advancements within the field of cumulative effects assessment to address these issues and improve our understanding of the consequences of our actions, many challenges in remain. Here, we detail advances and remaining challenges, and propose five priorities for addressing these challenges in the near future. In particular, we suggest prioritizing risk-based approaches that account for uncertainty in our understanding, and establishing underlying theory for when we expect particular impacts to occur. We also propose the need for a defined subdiscipline focused on cumulative effects, to help reduce the silos of research that are often disconnected, and to work towards a common set of definitions, methods and consistent use of open-data.